Safety and immunogenicity of ChAdOx1 85A prime followed by MVA85A boost compared with BCG revaccination among Ugandan adolescents who received BCG at birth: a randomised, open-label trial - Wajja, Anne; Nassanga, Beatrice; Natukunda, Agnes; Serubanja, Joel; Tumusiime, Josephine; Akurut, Helen; Oduru, Gloria; Nassuuna, Jacent; Kabagenyi, Joyce; Morrison, Hazel; Scott, Hannah; Doherty, Rebecca Powell; et al. (Elsevier Ltd, 2024)
Abstract BACKGROUNDBCG confers reduced, variable protection against pulmonary tuberculosis. A more effective vaccine is needed. We evaluated the safety and immunogenicity of candidate regimen ChAdOx1 85A-MVA85A compared with BCG revaccination among Ugandan adolescents.METHODSAfter ChAdOx1 85A dose escalation and age de-escalation, we did a randomised open-label phase 2a trial among healthy adolescents aged 12-17 years, who were BCG vaccinated at birth, without evident tuberculosis exposure, in Entebbe, Uganda. Participants were randomly assigned (1:1) using a block size of 6, to ChAdOx1 85A followed by MVA85A (on day 56) or BCG (Moscow strain). Laboratory staff were masked to group assignment. Primary outcomes were solicited and unsolicited adverse events (AEs) up to day 28 and serious adverse events (SAEs) throughout the trial; and IFN-γ ELISpot response to antigen 85A (day 63 [geometric mean] and days 0-224 [area under the curve; AUC).FINDINGSSix adults (group 1, n=3; group 2, n=3) and six adolescents (group 3, n=3; group 4, n=3) were enrolled in the ChAdOx1 85A-only dose-escalation and age de-escalation studies (July to August, 2019). In the phase 2a trial, 60 adolescents were randomly assigned to ChAdOx1 85A-MVA85A (group 5, n=30) or BCG (group 6, n=30; December, 2019, to October, 2020). All 60 participants from groups 5 and 6 were included in the safety analysis, with 28 of 30 from group 5 (ChAdOx1 85A-MVA85A) and 29 of 30 from group 6 (BCG revaccination) analysed for immunogenicity outcomes. In the randomised trial, 60 AEs were reported among 23 (77%) of 30 participants following ChAdOx1 85A-MVA85A, 31 were systemic, with one severe event that occurred after the MVA85A boost that was rapidly self-limiting. All 30 participants in the BCG revaccination group reported at least one mild to moderate solicited AE; most were local reactions. There were no SAEs in either group. Ag85A-specific IFN-γ ELISpot responses peaked on day 63 in the ChAdOx1 85A-MVA85A group and were higher in the ChAdOx1 85A-MVA85A group compared with the BCG revaccination group (geometric mean ratio 30·59 [95% CI 17·46-53·59], p<0·0001, day 63; AUC mean difference 57 091 [95% CI 40 524-73 658], p<0·0001, days 0-224).INTERPRETATIONThe ChAdOx1 85A-MVA85A regimen was safe and induced stronger Ag85A-specific responses than BCG revaccination. Our findings support further development of booster tuberculosis vaccines.FUNDINGUK Research and Innovations and Medical Research Council.TRANSLATIONSFor the Swahili and Luganda translations of the abstract see Supplementary Materials section.
Keywords: pulmonary tuberculosis; BCG revaccination among Ugandan adolescents; Vaccination; Uganda